(untitled) (Research, Society and Development, 2020)
The study aimed to describe relations between daily occupations and health perception from the point of view of adolescents. Qualitative study was conducted, using data collected in focus groups with 39 adolescents (13 to 16 years) attending a public school and analyzed using Thematic Content Analysis. The data were grouped into three categories: occupations in adolescence; health and adolescence; and positive and negative impacts of daily activities on adolescents’ health perception. A broad view of health was identified, with occupations seen as constituting activities carried out (alone or with others) in everyday life. Smartphone use stood out, not only as being one of the most commonly cited occupations, but also for reason of its negative impact on health perception. Difficulties talking to parents and mental health issues were specifically cited. The adolescents pointed to the importance of socioeconomic changes, measures to curb cell phone use, and, above all, stronger ties with parents, as possible health promotion strategies. The data analyzed indicate the need for and potential of health promotion strategies based on creating space for dialogue between parents and adolescents, to engage in critical reflection on everyday occupations and their impact on health.